Paesaggio e sostenibilità nei processi turistici. Un caso di sostenibilità sociale in Sardegna - Giuseppe Onni (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The tourism forms raise doubts about their capacity to be sustainable, especially compared against the landscape and the local society. Through a survey on the history of the tourism process in Sardinia and the analysis of some case studies we try to understand if instead is possible to imagine new forms of tourism. Sardinia itself is as an ideal place to study issues related to tourism, as along its coast, within fifty years, has developed a real tourist town, different in different places but with the characteristic of being always been guided by what is called a tourism ideology. The article questions whether it is possible, although within contexts compromised by tourism ideology , to find new forms of tourism capable of regenerating the relationship between them, the landscape and local societies.